2017
DOI: 10.3390/rel8020029
|View full text |Cite
|
Sign up to set email alerts
|

A Feasibility Study of Taste & See: A Church Based Programme to Develop a Healthy Relationship with Food

Abstract: Abstract:Holistic approaches which include a religious element are a promising intervention within obesity, but have not been explored in the UK. Objective: To conduct a feasibility study of a three-month, Christian-based intuitive-eating programme in a church. Methods: A total of 18 adults participated. Ethical approval was granted by Coventry University Ethics Committee. Participant and facilitator experience was investigated qualitatively. Results showed participants accepted the programme and engaged well … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 50 publications
0
11
0
Order By: Relevance
“…The design of the "Taste & See" programme and the protocol for testing the feasibility of this was previously reported in Religions (Lycett et al 2016). The results of the feasibility study, also previously reported in Religions, showed this programme could be run successfully by church volunteers and improvements in participants' mental well-being, emotional eating and quality-of-life were observed during and for six months after the programme (Patel et al 2017a). An embedded qualitative study of participant experience on this programme showed participants journeyed from shame and guilt to acceptance and freedom (Patel et al 2017b).…”
Section: Introductionmentioning
confidence: 62%
“…The design of the "Taste & See" programme and the protocol for testing the feasibility of this was previously reported in Religions (Lycett et al 2016). The results of the feasibility study, also previously reported in Religions, showed this programme could be run successfully by church volunteers and improvements in participants' mental well-being, emotional eating and quality-of-life were observed during and for six months after the programme (Patel et al 2017a). An embedded qualitative study of participant experience on this programme showed participants journeyed from shame and guilt to acceptance and freedom (Patel et al 2017b).…”
Section: Introductionmentioning
confidence: 62%
“…The pastoral care workers that provided spiritual-based dietary advice for young people in Patel et al study highlighted these ethical concerns (Patel et al 2017). These trainers felt out of their depth dealing with some of the existential and emotional issues that could arise as a request of addressing this particular topic (Patel et al 2017). Keenan (2017) thus calls for attention to spiritual safety, spiritual vulnerability, and spiritual risk in healthcare.…”
Section: Embracing Spirituality Across International Healthcare Contextsmentioning
confidence: 99%
“…Furthermore, there needs to be caution when attempting to address spiritual needs in healthcare, as (Keenan 2017) points out as some people may not wish to confront this issue, perhaps due to a lack of confidence. The pastoral care workers that provided spiritual-based dietary advice for young people in Patel et al study highlighted these ethical concerns (Patel et al 2017). These trainers felt out of their depth dealing with some of the existential and emotional issues that could arise as a request of addressing this particular topic (Patel et al 2017).…”
Section: Embracing Spirituality Across International Healthcare Contextsmentioning
confidence: 99%
See 2 more Smart Citations